247 BENCHMARKING STROKE SERVICES TO INFORM A QUALITY IMPROVEMENT INIAITIVE. (18th November 2021) - Loughlin, E; Gannon, E; Coughlan, A; Cunningham, N; Paulose, S; O'Brien, I; Ryan, R; Leahy, A; Lyons, D; Peters, C; McManus, J; O'Connor, M
Abstract: Background: Stroke is a leading cause of death and disability in Ireland. Continuous audit and quality improvement is essential in the delivery of stroke care where the evidence basis is constantly changing. This helps to ensure the delivery of high quality stroke care and compliance with evidenced based guidelines. We aimed to assess stroke care at an Irish university teaching hospital. Methods: Patients with a HIPE discharge diagnosis of Cerebral Infarction or Cerebral Haemorrhage (1st January-31 st December 2019) were identified through both the HIPE database and the institutional Stroke Portal. Data was benchmarked against national (Irish National Audit of Stroke 2019) and international (6th SSNAP Annual Report; American Heart Association, 2013) practice and used to inform a quality improvement strategy. Results: 419 patients were included (56.6% male, median 57 years). 75.9% were aged 65 years or older. We compared favourably with Irish National Audit of Stoke national indicators on the following: thrombolysis rates-10%; median door to needle time-60 mins; stroke unit admissions- 78.5%; median duration of symptoms- 3 hours 6 minutes; swallow assessment- 81.1%; in-patient mortality- 10.5%; rates of institutionalisation- 3.8%. Areas identified for improvement were: thrombectomy rates- 1.9%; median length of stay- 12 days; door to imaging time- median 104 minutes; mood screening- 11.5%. Conclusion: International and national data is a useful benchmark against which local hospitals can assess the quality of their service. By completing this quality improvement initiative we identified areas to target resources in our centre, including mood screening, swallow screening, thrombectomy rates, length of stay and time to neuroimaging. An ongoing quality improvement process using 'PDSA' methodology is being carried out with an annual audit to monitor progress.